2001
DOI: 10.1038/sj.mp.4000887
|View full text |Cite
|
Sign up to set email alerts
|

A genome screen of a large bipolar affective disorder pedigree supports evidence for a susceptibility locus on chromosome 13q

Abstract: Bipolar affective disorder is a severe mood disorder that afflicts approximately 1% of the population worldwide. Twin and adoption studies have indicated that genetic factors contribute to the disorder and while many chromosomal regions have been implicated, no susceptibility genes have been identified. In this present study, we undertook a 10 cM genome screen using 400 microsatellite markers in a large multigenerational bipolar pedigree consisting of 40 individuals, including six affecteds. We found strongest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…54 Region 13q was reportedly linked to schizophrenia in US 55 and Canadian 56 pedigrees, and to BP in US 5,15 and Australian pedigrees. 49 Reports that BP and schizophrenia may have susceptibility genes in common are consistent with the notion of a shared diathesis for the major psychoses. 17,57 They may also provide cross-validation of genetic findings and a basis for a broader view of disease phenotypes.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…54 Region 13q was reportedly linked to schizophrenia in US 55 and Canadian 56 pedigrees, and to BP in US 5,15 and Australian pedigrees. 49 Reports that BP and schizophrenia may have susceptibility genes in common are consistent with the notion of a shared diathesis for the major psychoses. 17,57 They may also provide cross-validation of genetic findings and a basis for a broader view of disease phenotypes.…”
Section: Discussionsupporting
confidence: 49%
“…48 Our finding at 10q21-24 is consistent with similar findings in another series of US pedigrees 15 and in German 9 and UK-Irish 47 families. Support for linkage to 13q was reported in two separate series of US pedigrees 5,15 and in a large Australian pedigree 49 (though at a more proximal site, on 13q14). Modest support for linkage to 17q was observed in a series of UK-Irish families.…”
Section: Discussionmentioning
confidence: 99%
“…Other chromosomal regions with suggestive linkage peaks in the genome-wide scan showed consistent results with other studies. The suggestive peaks at 4q and 13q are consistent with significant linkage results previously reported by our group in independent Australian BP cohorts, 32,42 while the 6q locus was reported as one of two confirmed BP loci in a genome-wide meta-analysis of 1067 families. 43 The supplementary markers were added to confirm the genome-wide linkage to 15q, and to gain greater location estimates for a BP susceptibility gene around the maximal genome scan marker D15S130.…”
Section: Discussionsupporting
confidence: 91%
“…59 These findings replicate and further clarify previous linkage findings in BD in these two chromosomal regions. 12,13,19,20,[60][61][62] They are especially interesting as the same regions may encompass susceptibility genes for schizophrenia. [63][64][65][66][67][68][69][70] Park et al 71 made similar conclusions in a study of psychotic BD in which most areas of linkage overlapped with those reported in previous investigations of schizophrenia.…”
Section: Psychotic Symptoms In Bdmentioning
confidence: 99%
“…In particular, findings in 4p, 4q, 8q, 10p, 12q24, 13q, 18p, 18q, 21q, and 22q have been supported by more than one study. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, these studies have not identified any specific genes, and a recent metaanalysis of available genome scans showed no regions with a conclusive evidence of linkage. 20 The relatively slow progress of gene-mapping efforts is often explained by the 'complex' nature of the illness and of the genotype-phenotype relation.…”
mentioning
confidence: 99%